Peran Filsafat Pendidikan Agama Kristen dalam Meningkatkan Potensi Manusia - Saturnina Elisa; Yonatan Alex Arifianto; Ririn Utari (Sekolah Tinggi Teologi Nusantara, 2023)
This is article aims to Provide an understanding of the role of the philoshopy of Christian religious educational in enhancing human potential that already exists in humans. The potenials possessed by humsnd are physical potential (physical), spiritual potential (spiritual), and reason (mind). So to in increase the human potential that is owned, the philosophyof education which is currently growing day by day is growing so that as a result the potential of every human beingt can be developed and increased. Through the role of Christian religious education philosophy in increasing human potential, using descriptive qualitative methods the researchers analyzes it with literature studies to be able to provide an understanding of the role of educational philosophy in increasing human potential in order to make an educational philosophy a good influence in developing an enhancing a human potential it self. AbstrakArtikel ini bertujuan memberikan suatu pengertian mengenai peran filsafat pendidikan dalam meningkatkan potensi manusiawi yang secara lahiriah telah ada dalam diri manusia. Maka untuk meningkatkan potensi manusiawi yang dimiliki tersebut filsafat pendidikan yang dewasa ini semakin hari semakin berkembang sehingga hasilnya potensi yang dimiliki setiap manusiawi dapat dikembangkan dan semakin . Melalui peran filsafat pendidikan dalam meningkatkan potensi manusiawi, dengan metode kualitatif deskriptif peneliti menganalisis dengan studi pustaka untuk dapat memberikan suatu pemahaman mengenai peran filsafat pendidikan dalam meningkatkan potensi manusiawi agar dapat menjadikan suatu filsafat pendidikan sebagai pengaruh yang baik dalam mengembangkan dan meningkatkan suatu potensi manusiawi itu sendiri. Kata Kunci: filsafar, pendidikan agama Kristen, potensi manusia